Dampak Ketahanan Pangan dan Keanekaragaman Diet terhadap Stunting pada Anak - Sitti Rahmatia; Simunati Simunati; Rosnah Rosnah; Sukmawati Sukmawati (Celebes Health Journal, 2026)
Background: Stunting remains a major public health problem, particularly in developing countries, and is closely linked to inadequate food access and poor dietary quality. Objective: This study aimed to analyze the impact of household food security and dietary diversity on stunting among children Methods: A cross-sectional study was conducted in Pakeng Village, within the working area of the Lembang Public Health Center, from May to July 2025, involving 80 respondents. Data were collected from health center databases and structured interviews. Stunting status was assessed using height-for-age indicators, while food security and dietary diversity were measured using standardized approaches. Results: Bivariate analysis showed significant associations between all independent variables and stunting (p <0.05). Multivariate analysis revealed that severe household food insecurity was the most dominant factor (AOR = 6.90), followed by low dietary diversity. The model demonstrated good predictive performance. Conclusions: Improving food security and dietary diversity isessential to reduce the burden of Stunting.